A method for early evaluation of a recently introduced technology by deriving a comparative group from existing clinical data: a case study in external support of the Marfan aortic root. Issue 2 (2nd March 2012) - Treasure, Tom; Crowe, Sonya; Chan, K M John; Ranasinghe, Aaron; Attia, Rizwan; Lees, Belinda; Utley, Martin; Golesworthy, Tal; Pepper, John
Abstract : Objective: During the early phase of evaluation of a new intervention, data exist for present practice. The authors propose a method of constructing a fair comparator group using these data. In this case study, the authors use the example of external aortic root support, a novel alternative to aortic root replacement. Design: A matched comparison group, of similar age, aortic size and aortic valve function to those having the novel intervention, was constructed, by minimization, from among patients having conventional aortic root replacement in other hospitals during the same time frame. Setting: Three cardiac surgical units in England. Patients: The first 20 patients, aged 16–58 years with aortic root diameters of 40–54 mm, having external support surgery were compared with 20 patients, aged 18–63 years and aortic root diameters of 38–58 mm, who had conventional aortic root replacement, between May 2004 and December 2009. Interventions: A pliant external mesh sleeve, customised by computer-aided design, encloses the whole of the ascending aorta. The comparator group had conventional aortic root replacement, 16 valve-sparing and four with composite valved grafts. Main outcome measures: Duration of cardiopulmonary bypass (CPB), myocardial ischaemic time, blood loss and transfusion of blood, platelets and clotting factors. Results: Comparing total root replacement and customised aortic root support surgery: CPB (median (range)) was 134 (52–316) versus 0 (0–20) min; myocardial ischaemia 114 (41–250) versus 0 (0–0) min; 4 h blood loss was 218 (85–735) versus 50 (25–400) ml; and 9/18 had blood transfusion, 9/18 platelets and 12/18 fresh frozen plasma after root replacement versus 1/20, 0/20 and 0/20, respectively, for the novel surgery. Conclusions: Avoidance or large reductions in CPB, myocardial ischaemia and blood product usage were achieved with the novel surgery. These data are of use in decision analysis and health economic evaluation and are available early in evaluation before randomised trial data are available.